Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
Calculus 2 Area between curves problem?
What would the area be between these two curves, out to 5 decimal places?
(16/(1+x^4)) and 8x^2
4 Answers
- Roger the MoleLv 73 years agoFavorite Answer
Looking at their graphs, the two functions intersect at x = -1 and x = 1, and over that interval 16/(1+x^4) has the largest value.
So the desired area can be evaluated by:
x = 1
∫ (16/(1+x^4)) - 8x^2 dx
x = -1
which, after a long integration, is equivalent to:
4 √2 (π + 2 coth^-1 (√2)) - 16/3
where "coth^-1" is the inverse function of the hyperbolic cotangent.
That expression evaluates to:
22.40980226154382
(If it was my problem, I would write a computer program to use the Newton-Cotes formulas or Runge–Kutta methods to do the integration numerically and avoid the messy explicit integration alluded to above. But I have that opinion because I am more comfortable with programming than with complicated integration.)
(Later update: since the questions were coming in slowly to YA, I went ahead and did that, and I got 22.409802261583, so even beyond the requested 5 decimal places I agree with Wolfram's results, along with two other answerers here.)
For the confirmed nerds, here is the Perl program I wrote:
$z = 1/2**18;
for ($x = $z/2; $x < 1; $x += $z) {
$y = (16/(1 + $x**4)) - 8 * $x**2;
$s += $y;
}
print $s * $z * 2;
Source(s): http://www.wolframalpha.com/input/?i=plot+y+%3D+(1... http://www.wolframalpha.com/input/?i=%E2%88%AB+(16... - alexLv 73 years ago
intersect 16/(1+x^4) = 8x^2 ---> x=-1, 1
Area = ∫ (16/(1+x^4) - 8x^2) dx , over [-1,1] = 16∫ (2/(1+x^4) - x^2) dx , over [0,1]
2/(1+x^4) = 2/[(x^2 + x√2 + 1)(x^2 - x√2 + 1)] = (ax+b)/(x^2 + x√2 + 1) + (cx+d)/(x^2 - x√2 + 1)
find a, b ,c , d
then integrate
.....
---> Area = 16∫ (2/(1+x^4) - x^2) dx , over [0,1] = 22.40980
- Anonymous3 years ago
16/(1 + (x^4)) = 8*(x^2);
Let u = x^2;
16/(1 + (u^2)) = 8u
16 = 8u*(1 + (u^2))
2 = u*(1 + (u^2));
2 = u + (u^3);
By look at this one of the answer is u = 1
(u^3) + u - 2 = 0;
(u - 1)*((u^2) + u + 2) = 0;
The only real answer is u = 1; x^2 = 1; x = +/- 1;
int_(-1)^(1) ((16/((x^4) + 1)) - (8*(x^2))) dx; this is an even function, therefore
int_0^(1) ((32/((x^4) + 1)) - (16*(x^2))) dx;
int_0^(1) 32/((x^4) + 1) dx - (16/3);
int_0^(1) sum_(n = 0)^(infinity) ((-1)^n)*(32)*(x^(4n)) dx - (16/3);
[sum_(n = 0)^(infinity) ((-1)^n)*(32)*(x^(4n + 1))/(4n + 1) from F(x = 1) - F(x = 0)] - (16/3);
(sum_(n = 0)^(infinity) (32)*((-1)^n)/(4n + 1)) - (16/3);
- 3 years ago
Find where they intersect
16 / (1 + x^4) = 8x^2
16 = 8 * x^2 * (1 + x^4)
2 = x^2 * (1 + x^4)
x^2 = t
2 = t * (1 + t^2)
2 = t + t^3
t = 1 is a solution, so t - 1 is a root
t^3 + t - 2 = 0
(t - 1) * (at^2 + bt + c) = 0
(t - 1) * (at^2 + bt + c) = t^3 + t - 2
at^3 + bt^2 + ct - at^2 - bt - c = t^3 + 0t^2 + t - 2
a = 1
b - a = 0
c - b = 1
-c = -2
b = a
b = 1
c - 1 = 1
c = 2
(t - 1) * (t^2 + t + 2) = 0
t^2 + t + 2 = 0
t = (-1 +/- sqrt(1 - 8)) / 2
t = (-1 +/- i * sqrt(7)) / 2
t = x^2
t = 1
1 = x^2
-1 , 1 = x
Confirm that both are continuous and differentiable along the interval. They are. Find which one is greater
f(0) = 8 * 0^2 = 0
g(0) = 16 / (1 + 0^4) = 16
16 / (1 + x^4) > 8x^2 along the interval
Now we integrate
16 * dx / (1 + x^4) - 8 * x^2 * dx
You can follow the steps of integrating 16 * dx / (1 + x^4) here:
https://www.symbolab.com/solver/indefinite-integra...
Let's just apply our limits
2 * sqrt(2) * (ln|x^2 + sqrt(2) * x + 1| - ln|x^2 - sqrt(2) * x + 1| - 2 * arctan(1 - sqrt(2) * x) + 2 * arctan(1 + sqrt(2) * x))
2 * sqrt(2) * (ln|1 + sqrt(2) + 1| - ln|1 - sqrt(2) + 1| - 2 * arctan(1 - sqrt(2)) + 2 * arctan(1 + sqrt(2))) - 2 * sqrt(2) * (ln|1 - sqrt(2) + 1| - ln|1 + sqrt(2) + 1| - 2 * arctan(1 + sqrt(2)) + 2 * arctan(1 - sqrt(2))) =>
2 * sqrt(2) * (ln|2 + sqrt(2)| - ln|2 - sqrt(2)| - ln|2 - sqrt(2)| + ln|2 + sqrt(2)| + 2 * arctan(1 + sqrt(2)) - 2 * arctan(1 - sqrt(2)) + 2 * arctan(1 + sqrt(2)) - 2 * arctan(1 - sqrt(2)) =>
2 * sqrt(2) * (2 * ln|2 + sqrt(2)| - 2 * ln|2 - sqrt(2)| + 4 * arctan(1 + sqrt(2)) - 4 * arctan(1 - sqrt(2))) =>
2 * sqrt(2) * 2 * (ln|2 + sqrt(2)| - ln|2 - sqrt(2)| + 2 * (arctan(1 + sqrt(2)) - arctan(1 - sqrt(2)))) =>
4 * sqrt(2) * (ln|(2 + sqrt(2)) / (2 - sqrt(2))| + 2 * (arctan(1 + sqrt(2)) - arctan(1 - sqrt(2)))) =>
4 * sqrt(2) * (ln|(4 + 4 * sqrt(2) + 2) / (4 - 2)| + 2 * (arctan(1 + sqrt(2)) - arctan(1 - sqrt(2)))) =>
4 * sqrt(2) * (ln|3 + 2 * sqrt(2)| + 2 * (arctan(1 + sqrt(2)) - arctan(1 - sqrt(2))))
k = arctan(1 + sqrt(2)) - arctan(1 - sqrt(2))
k = arctan(a) - arctan(b)
tan(k) = tan(arctan(a) - arctan(b))
tan(k) = (tan(arctan(a)) - tan(arctan(b)) / (1 + tan(arctan(a)) * tan(arctan(b)))
tan(k) = (a - b) / (1 + a * b)
tan(k) = (1 + sqrt(2) - 1 + sqrt(2)) / (1 + (1 - 2)))
tan(k) = 2 * sqrt(2) / 0
tan(k) is undefined, so k = pi/2 (or 3pi/2)
4 * sqrt(2) * (ln|3 + 2 * sqrt(2)| + 2 * (arctan(1 + sqrt(2)) - arctan(1 - sqrt(2)))) =>
4 * sqrt(2) * (ln|3 + 2 * sqrt(2)| + 2 * (pi/2)) =>
4 * sqrt(2) * (ln|3 + 2 * sqrt(2)| + pi)